PENGEMBANGAN IPAS LKPD BERBASIS STEAM-PjBL UNTUK MENINGKATKAN LITERASI ILMU PENGETAHUAN SISWA - Yulianti, Dwi; Apri Wahyudi, Apri Wahyudi; Roy Kembar Habibi, Roy Kembar Habibi; Fitriadi, Fitriadi; Putra You Hendra, Putra You Hendra (UNDIKMA, 2026)
This study aims to develop Student Worksheets (LKPD) for Natural and Social Sciences (IPAS) based on the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach and the Project Based Learning (PjBL) model to improve the science literacy of fourth-grade elementary school students. The research method used was Research and Development (R&D) with the 4D development model (Define, Design, Develop, Disseminate). The test subjects consisted of 20 students and 3 educators at an elementary school in Bandar Lampung City. The results of validation by media, language, and material experts show that the developed LKPD is considered highly valid with an average Aiken's V coefficient above 0.90. Practicality tests show that the LKPD is rated